Predictors of ACEI/ARB therapy in patients with hypertrophic cardiomyopathy : results of a national registry - Martins, E. (2018)
© The European Society of Cardiology 2018. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org